The economic and political arguments for and against social clauses - Christoph Scherrer (Intereconomics, 1996)
The globalisation of markets is calling national employment and social legislation increasingly into question, so that not only the international trade union organisations but also the Clinton Administration are calling for workers' rights to be embodied in trade agreements. This article deals both with the fundamental question whether international labour standards serve a useful purpose and the more specific question whether trade agreements are a suitable way of enforcing minimum standards.
Keywords: 330; Social Standards